2008
DOI: 10.1038/sj.bjc.6604686
|View full text |Cite
|
Sign up to set email alerts
|

Use of photosensitising diuretics and risk of skin cancer: a population-based case–control study

Abstract: Diuretics have photosensitising properties. However, little is known about how these diuretics affect the risk of skin cancers. In North Jutland County, Denmark, we investigated whether the use of photosensitising diuretics was associated with an increased risk for developing basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and malignant melanoma (MM). From the cancer registry, we identified primary cases of BCC, SCC and MM during the period of 1989 -2003. We selected four population controls for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
160
3
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(184 citation statements)
references
References 30 publications
12
160
3
9
Order By: Relevance
“…Possible associations with skin cancer risks were observed with consumption of parsnips (CMM) and with the use of thiazines (BCC), thiazide diuretics (SCC) and cardiac drugs (CMM), as is consistent with the known photosensitizing potential of these food items and drugs. [15][16][17][18][19][20][40][41][42] Of the food and drug associations studied, only a negative association with pomegranate and ciprofloxacin and a positive association with thiazide diuretics remained significant after correction for multiple testing, germane to previously reported association with increased risks of SCC, CMM and BCC. 42,46 When we further analysed the negative association with ciprofloxacin (Table 5), the numbers taking this antibiotic daily for more than 3 months were low (37 controls, 10 BCC, 7 SCC, 12 CMM) and were almost all from Italy, Germany and Poland.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Possible associations with skin cancer risks were observed with consumption of parsnips (CMM) and with the use of thiazines (BCC), thiazide diuretics (SCC) and cardiac drugs (CMM), as is consistent with the known photosensitizing potential of these food items and drugs. [15][16][17][18][19][20][40][41][42] Of the food and drug associations studied, only a negative association with pomegranate and ciprofloxacin and a positive association with thiazide diuretics remained significant after correction for multiple testing, germane to previously reported association with increased risks of SCC, CMM and BCC. 42,46 When we further analysed the negative association with ciprofloxacin (Table 5), the numbers taking this antibiotic daily for more than 3 months were low (37 controls, 10 BCC, 7 SCC, 12 CMM) and were almost all from Italy, Germany and Poland.…”
Section: Discussionmentioning
confidence: 92%
“…15,16 Furthermore, in case-control studies reported use of photosensitizing drugs has been associated with increased occurrence of BCC, SCC and actinic keratosis 40,41 and photosensitizing diuretics have been found to associate with increased risks of SCC and CMM. 42 Drug-associated photosensitivity may reflect conversion to electrophiles and ⁄or sources of reactive oxygen species, while other drugs interact synergistically with UV radiation. The immunosuppressant azathioprine, for instance, increases skin sensitivity to UVA by generating 6-thioguanine DNA photoproducts and thus making azathioprine and UVA synergistically mutagenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many drugs, including psoralens, tetracyclines, fluoroquinolones, nonsteroidal anti-inflammatory agents, and amiodarone, are known to have photosensitizing properties (1)(2)(3)(4)(5)(6). There is evidence that photosensitization of the skin followed by exposure to UV radiation (UVR) enhances the risk of sunburns and photo damage to the skin, which might increase the risk of skin cancer (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…2,7,8) and cutaneous malignant melanoma (CMM) (9). Furthermore, photosensitizing diuretics have been shown to increase the risk of skin malignancies in humans (4), and fluoroquinolone antibiotics have been shown to induce skin lesions (5), SCCs in particular, in mice exposed to UVR (10).…”
Section: Introductionmentioning
confidence: 99%